Farmers welfare in Ghana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
According to Mr. A N Moomen, of the new Agricultural Insurance Scheme and Flight Lieutenant Joe B Atiemo, of the Ghana Cocoa Board, a Farmers' Welfare Fund is to be established in Ghana.